Opportunities to integrate new approaches in genetic toxicology: An ILSI‐HESI workshop report. (6th December 2014) - Zeiger, Errol; Gollapudi, Bhaskar; Aardema, Marilyn J.; Auerbach, Scott; Boverhof, Darrell; Custer, Laura; Dedon, Peter; Honma, Masamitsu; Ishida, Seiichi; Kasinski, Andrea L.; Kim, James H.; Manjanatha, Mugimane G.; et al.
Abstract : Genetic toxicity tests currently used to identify and characterize potential human mutagens and carcinogens rely on measurements of primary DNA damage, gene mutation, and chromosome damage in vitro and in rodents. The International Life Sciences Institute Health and Environmental Sciences Institute (ILSI‐HESI) Committee on the Relevance and Follow‐up of Positive Results in In Vitro Genetic Toxicity Testing held an April 2012 Workshop in Washington, DC, to consider the impact of new understanding of biology and new technologies on the identification and characterization of genotoxic substances, and to identify new approaches to inform more accurate human risk assessment for genetic and carcinogenic effects. Workshop organizers and speakers were from industry, academe, and government. The Workshop focused on biological effects and technologies that would potentially yield the most useful information for evaluating human risk of genetic damage. Also addressed was the impact that improved understanding of biology and availability of new techniques might have on genetic toxicology practices. Workshop topics included (1) alternative experimental models to improve genetic toxicity testing, (2) Biomarkers of epigenetic changes and their applicability to genetic toxicology, and (3) new technologies and approaches. The ability of these new tests and technologies to be developed into tests to identify and characterize genotoxic agents; to serve as a bridge between in vitro and in vivo rodent, or preferably human, data; or to be used to provide dose response information for quantitative risk assessment was also addressed. A summary of the workshop and links to the scientific presentations are provided. Environ. Mol. Mutagen. 56:277–285, 2015. © 2014 Wiley Periodicals, Inc.